The gene : an intimate history [videorecording (DVD)] - Cieri, David (Distributed by PBS Distribution, 2020)
Scientific genetics, little more than a century old, holds at once the promise of eradicating disease and the threat of altering the very essence of what it means to be human. It traces the dizzying evolution of this new science as researchers race to identify treatments for genetic diseases, such as cancer and sickle cell anemia, and to perfect tools for rewriting DNA.